Asian consortium on radiation dose of pediatric cardiac CT (ASCI-REDCARD). - Hui, Peter; Goo, Hyun; Du, Jing; Ip, Janice; Kanzaki, Suzu; Kim, Young; Kritsaneepaiboon, Supika; Lilyasari, Oktavia; Siripornpitak, Suvipaporn; Hui, Peter K T; Goo, Hyun Woo; Ip, Janice J K; et al. (Pediatric Radiology, 2017)
Background: With incremental utilization of pediatric cardiac CT in congenital heart disease, it is imperative to define its current radiation dose levels in clinical practice in order to help imagers optimize CT protocols, particularly in Asia and other developing countries where CT physicists are not readily available.Objective: To evaluate current radiation dose levels and influencing factors in cardiac CT in children with congenital heart disease in Asia by conducting a retrospective multi-center, multi-vendor study.Materials and Methods: We included 1,043 pediatric cardiac CT examinations performed in 8 centers between January 2014 and December 2014 to evaluate congenital heart disease. In five weight groups, we calculated radiation dose metrics including volume CT dose index, size-specific dose estimate, dose-length product and effective dose. Age at CT exam, gender, tube voltage, scan mode, CT indication and image reconstruction algorithm were analyzed to learn whether they influenced CT radiation dose.Results: Volume CT dose index, size-specific dose estimate, dose-length product and effective dose of pediatric cardiac CT showed variations in the range of 4.3-23.8 mGy, 4.9-17.6 mGy, 55.8-501.3 mGy∙cm and 1.5-3.2 mSv, respectively, within five weight groups. Gender, tube voltage, scan mode and cardiac function assessment significantly influenced CT radiation dose.Conclusion: This multi-center, multi-vendor study demonstrated variations in radiation dose metrics of pediatric cardiac CT reflecting current practice in Asia. Gender, tube voltage, scan mode and cardiac function assessment should be considered as essential radiation dose-influencing factors in developing optimal pediatric cardiac CT protocols.